2018
DOI: 10.1016/j.mcat.2018.05.025
|View full text |Cite
|
Sign up to set email alerts
|

A highly active and synergistic Pt/Mo2C/Al2O3 catalyst for water-gas shift reaction

Abstract: Evgeny (2018) A highly active and synergistic Pt/Mo 2 C/Al 2 O 3 catalyst for water-gas shift reaction. Molecular Catalysis, AbstractCatalysts consisting of Pt and Cu supported on Mo2C/η-Al2O3, Mo2C/γ-Al2O3 or Mo2C were prepared and used for the low-temperature water gas shift reaction. The catalysts were characterized by elemental analysis, X-ray diffraction (XRD), temperature-programmed reduction (TPR), X-ray photoelectron spectroscopy (XPS) and scanning electron microscopy (SEM). The catalysts were studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 34 publications
(38 reference statements)
0
15
0
Order By: Relevance
“…The performance of Pt catalysts loaded on different supports, Mo 2 C/η-Al 2 O 3 , Mo 2 C/γ-Al 2 O 3 , or Mo 2 C, were tested by Osman et al for low-temperature WGS reaction [34], where Pt/Mo 2 C/η-Al 2 O 3 was found to be a promising catalyst with 44% CO conversion at 180°C. However, 4 wt% Pt-Mo 2 C ( Fig.…”
Section: Noble Metal Basedmentioning
confidence: 99%
See 1 more Smart Citation
“…The performance of Pt catalysts loaded on different supports, Mo 2 C/η-Al 2 O 3 , Mo 2 C/γ-Al 2 O 3 , or Mo 2 C, were tested by Osman et al for low-temperature WGS reaction [34], where Pt/Mo 2 C/η-Al 2 O 3 was found to be a promising catalyst with 44% CO conversion at 180°C. However, 4 wt% Pt-Mo 2 C ( Fig.…”
Section: Noble Metal Basedmentioning
confidence: 99%
“…Along with synthesis of the Pt@TiO 2 yolk/shell nanospheres [33]. g SEM image of deactivation over 85 h of time on stream (TOS) at 250°C temperature, maintaining over 70% CO conversion [34]. This improved performance was attributed to a uniform distribution of smaller Pt nanoparticles on Mo 2 C structure compared to other supports.…”
Section: Noble Metal Basedmentioning
confidence: 99%
“…Owing to these excellent properties, MoS 2 and its based nanocomposites have been extensively studied in many fields and applications like catalysis, energy storage, supercapacitors, and Li-ion batteries (Osman et al 2018).…”
Section: Molybdenum Disulfidementioning
confidence: 99%
“…The supports significantly affect the catalytic performance in this reaction. Osman et al found that using acidic supports led to different interaction and synergetic effect between the two most active phases of Pt metal and Mo 2 C, thus the acidity played a crucial role herein [52]. Metal nanoparticles supported on reducible metal oxides show great catalytic performance in this field.…”
Section: Water-gas Shift Reaction (Wgsr)mentioning
confidence: 99%